Thermal Percolation of Antiperovskite Superionic Conductor into Porous MXene Scaffold for High‐Capacity and Stable Lithium Metal Battery. Issue 11 (9th October 2022) - Li, Yang; Kong, Long; Yang, Haochen; Li, Shuai; Deng, Zhi; Li, Shuo; Wang, Liping; Lee, Jim Yang; Zhao, Yusheng; Chen, Po‐Yen
Abstract: Lithium metal battery is considered an emerging energy storage technology due to its high theoretical capacity and low electrochemical potential. However, the practical exploitations of lithium metal batteries are not realized because of uncontrollable lithium deposition and severe dendrite formation. Herein, a thermal percolation strategy is developed to fabricate a dual‐conductive framework using electronically conductive Ti3 C2 T x MXene aerogels (MXAs) and Li2 OHCl antiperovskite superionic conductor. By melting Li2 OHCl at a low temperature, the molten antiperovskite phase can penetrate the MXA scaffold, resulting in percolative electron/ion pathways. Through density functional theory calculations and electrochemical characterizations, the hybridized lithiophilic (MXA)−lithiophobic (antiperovskite) interfaces can spatially guide the deposition of lithium metals and suppress the growth of lithium dendrites. The symmetric cell with MXA–antiperovskite electrodes exhibits superior cycling stability at high areal capacities of 4 mAh cm −2 over 1000 h. Moreover, the full cell with MXA−antiperovskite anode and high‐loading LiFePO4 cathode demonstrates high energy and power densities (415.7 Wh kgcell −1 and 231.0 W kgcell −1 ) with ultralong lifespans. The thermal percolation of lithium superionic conductor into electronically conductive scaffolds promises an efficient strategy to fabricate dual‐conductive electrodes, which benefits the development of dendrite‐free lithium metal anodes with high energy/power densities. Abstract : By integrating low‐melting‐point Li2 OHCl antiperovskite superionic conductor into electronically conductive MXene aerogel (MXA) scaffold via scalable thermal percolation approach, a homogenous and dual‐conductive MXA–antiperovskite framework is fabricated for stable lithium metal anodes. The percolative electron/Li + pathways and hybridized lithiophilic (MXA)–lithiophobic (antiperovskite) interfaces throughout the framework modulate spatially confined lithium deposition, benefiting high‐energy‐density and long‐term lifespan lithium metal batteries.